The monsters in my life: An analysis of violence in Pelea de Gallos by María Fernanda Ampuero - Villavicencio Quinde, Manuel Gonzalo (2025)
The objective of this essay is to analyze the mechanisms of counterpower in Pelea de Gallos (2018) by María Fernanda Ampuero, through the lens of the category of the monstrous, in order to reveal how female characters who have been subjected to physical and symbolic violence challenge, resist, and subvert the patriarchal paradigm. This study draws on the theoretical contributions of Canguilhem (1966), Gutiérrez Mouat (2004), Cohen (1996), Giorgi (2009), and Koricancic (2011), among others, regarding the evolution and conceptualization of the monstrous, and how this category becomes a device of defense against the abuse experienced by the protagonists during childhood, adolescence, and adulthood. The work of Foucault (1976) is also central, particularly his reflections on power and counter power relations, and on biopower, especially in relation to the control of bodies.